2021
DOI: 10.3389/fonc.2021.633794
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of EGFR Signaling Is a Latent Strategy for the Improvement of Prognosis of HPV-Induced Cancer

Abstract: Human papillomavirus (HPV) is a double-stranded DNA (dsDNA) virus, and its high-risk subtypes increase cancer risks. However, the mechanism of HPV infection and pathogenesis still remain unclear. Therefore, understanding the molecular mechanisms and the pathogenesis of HPV are crucial in the prevention of HPV-related cancers. In this study, we analyzed cervix squamous cell carcinoma (CESC) and head and neck carcinoma (HNSC) combined data to investigate various HPV-induced cancer common features. We showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…EGFR signaling can also be affected by the Hippo/YAP pathway, which eventually influences cancer progression in HPV + cervical cancer [ 80 ]. Qiu et al reported that E7 protein downregulates EGFR, which downregulates the phosphorylation of EGFR and inhibits EGFR downstream pathway that in turn induces a better prognosis [ 81 ]. Moreover, Cai et al identified a mechanism of immunoregulation mediated via the STING-TBK1- nuclear factor-kappa B (NF-κB) pathway in HPV + cervical cancer [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…EGFR signaling can also be affected by the Hippo/YAP pathway, which eventually influences cancer progression in HPV + cervical cancer [ 80 ]. Qiu et al reported that E7 protein downregulates EGFR, which downregulates the phosphorylation of EGFR and inhibits EGFR downstream pathway that in turn induces a better prognosis [ 81 ]. Moreover, Cai et al identified a mechanism of immunoregulation mediated via the STING-TBK1- nuclear factor-kappa B (NF-κB) pathway in HPV + cervical cancer [ 82 ].…”
Section: Introductionmentioning
confidence: 99%